(untitled) (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: Vocal cord polyp usually arises from the epithelium and the lamina propria. Minimally invasive dissection procedures are employed to treat these vocal cord polyp for an effective outcome. Two types of microsurgical techniques were developed gradually and practiced namely, the conventional laryngeal microsurgery, which involves the use of cold instruments and the laryngeal laser micro-surgery. Objective: To compare the conventional cold dissection and CO2 laser methods in treatment of vocal cord polyp. Methods: A randomized prospective study was conducted at the Department of Otolayngology- Head & Neck Surgery, at Bangabondhu Sheikh Muzib Medical University (BSMMU) between July 2017 and June 2019. A total of 60 cases were studied on the following parameters: a. Visual analysis on stroboscopy b. Voice analysis –GRBAS (grade, roughness, breathiness, asthenia, strain) indices c. Duration of surgery d. Peroperative bleeding. Results: During first postoperative assessment, both groups had the normal symmetrical waves, while 50% of cases still had aperiodicity but all patients had the near normal periodicity in the second postoperative assessment. Regarding glottic closure, during preoperative assessment, almost all patients had incomplete glottic closure due to mass lesion as polyps. During first postoperative assessment, glottic closure was found to be better in group B (83% of cases) than group A (76% of cases), while during second postoperative assessment, all patients of both groups had around 95% glottic closure. The mean duration oflaser technique (7.1 ± 1.1 minutes) was less than the conventional technique time (15.6 ± 1.9 minutes), also mean of operative bleeding of laser technique (zero pack) is less than the conventional two(2 packs). Conclusion: There is no significant difference between both groups in all parameters except operative time and bleeding, as laser technique has less time and clear field. Bangladesh J Otorhinolaryngol; April 2021; 27(1): 17-24